Effect of hypermagnesaemia on plasma and salivary magnesium, calcium, phosphate, sodium and potassium concentrations in sheep - DUA, K (The Indian Journal of Animal Sciences, 2014)
The present study was undertaken to have a better understanding about the mineral and electrolyte alterations in the plasma and saliva associated with magnesium infusion. Five experiments were conducted in 3 trained sheep, each with a large rumen cannula. The total collection of saliva was done by slipping a salivary collector at the base of the oesophagus. After 60 min of stabilization, a loading dose of 15 ml magnesium sulphate (25%, w/v) was given intravenously and this solution subsequently infused for 120 min @ 12 ml/hr with the help of an infusion pump. Hypophosphataemia and to some extent hypocalcaemia were observed which may be because of decrease in the parathyroid hormone and increased level of calcitonin in the circulation. In the saliva, the salivary Na: K ratio showed a significant increase following magnesium sulphate infusion. The result of present study has important implications in the treatment of hypomagnesaemia .